The Judge’s Consideration in Sentencing Illegal Drug Distribution in Case No.105/Pid. Sus/2019/Pn. Slw - Aisy Idzati (Universitas Negeri Semarang, 2021)
The rampant circulation of illegal drugs shows that the level of public awareness is still low against the risk of drug use that does not meet the requirements of BPOM. Case Number 105/Pid.sus/2019/PN.Slw is a case about illegal drug trafficking without permission from BPOM. This research was conducted to find out the considerations used by judges in sentencing in Case Number 105/Pid.sus/2019/PN.Slw. This study uses a qualitative approach. The type of research used is sociological juridical. Secondary data is collected through library studies. Primary data is collected through interviews. The results showed that the judge, in his decision, used balance theory, scientific theory and ratio decidendi theory in order to get a fair verdict in handing down the verdict.